The Theory Practices Gap among Nursing and Midwifery Students in Palestine - Amro, Nawaf RN; Ayham Slimi, Ayat Al Sous, Shatha Shkherat, Haya Nahli, Rajeh Hassasneh, (International Journal of Innovative Research in Medical Science, 2018)
Clinical experience is one of the most significant sources of stress and anxiety producing components of the nursing program. Clinical training, not only gives students the opportunity to transfer what they have learnt during theory into the unfamiliar and complex clinical practice environments. It also helps students learn a variety of skills, such as how to establish communication, make decisions and work as a member of a team. The purpose of this study was to identify nursing and midwifery students’ problems during clinical practice at the baccalaureate nursing program in Palestine. Descriptive cross-sectional study design was utilized. A stratified sample of 340 nursing and midwifery students was recruited. Data were collected on a self-administered questionnaire. The sample was derived from students who had experienced clinical practice among the students in the department of nursing and midwifery sciences in Al-Quds University in Palestine. The study started with 340 students, including 155 males and 185 females. The final analysis was conducted with 330 participants comprising 151 (45.8%) males and 179 (54.2%) females. The majority of respondents stated that they did perceive a difference between what they were taught in the classroom compared to what was used in their clinical experiences with 237 (71.8%) responding yes and 93 (28.2%) responding no. Approximately, half of the students perceived the extent of the gap between theoretical & practical side with 138 (41.8%) responding big. Therefore, nursing facilitators should train and make more researches to identifying more problems and working to enhancing these problems to have a professions nursing and midwifery in our life.